Effects of bariatric surgery for knee complaints in (morbidly) obese adult patients: a systematic review. Issue 2 (8th December 2014) - Groen, V. A; van de Graaf, V. A.; Scholtes, V. A. B.; Sprague, S.; van Wagensveld, B. A; Poolman, R. W.
Summary Obesity is a major risk factor for the development of knee osteoarthritis, and over the past 30 years the prevalence of obesity has more than doubled. In an advanced‐stage knee osteoarthritis is treated with total knee arthroplasty, and the demand for primary total knee arthroplasties is expected to grow exponentially. However, total knee arthroplasty in obese patients is associated with more complications, longer hospital stay and higher costs. We aimed to determine the effects of bariatric surgery on knee complaints in (morbidly) obese (body mass index >30 kg m−2) adult patients. The Cochrane Central Register of Controlled Trials, MEDLINE, EMBASE, TRIP, BIOSIS‐Previews and reference lists of retrieved publications were systematically searched from earliest available up to 20 April 2014 for any English, German, French and Dutch studies. There was no restriction on study design. We included studies on the effect of surgically induced weight reduction on knee complaints in (morbidly) obese adult patients, with a minimal follow‐up of 3 months. Studies on the effects of lipectomy or liposuction and studies in which patients had already received a total knee arthroplasty were excluded. Thirteen studies were included in this systematic review with a total of 3, 837 patients. Although different assessment tools were used, an overall significant improvement in knee pain was seen in 73% out of the used assessments. All studies measuring intensity of knee pain, knee physical function and knee stiffness showed a significant improvement after bariatric surgery. The quality of evidence was very low or too low for most of the included studies and moderate for one study. Bariatric surgery with subsequent marked weight loss is likely to improve knee pain, physical function and stiffness in (morbidly) obese adult patients. However, with the current available evidence, there is need for high‐quality studies.